Car Park Availability Assessment in Muar Town Using GIS - Bukari, Saifullizan Mohd (International Journal of Integrated Engineering, 2019)
Parking is an important element in providing a broad range of transportation planning policy in an area. The increasing demand for parking space, particularly in the downtown area requires the provision of adequate parking area, comfortable and safe with regard to the ability of the current land use in urban areas. The development and progress in a certain area will cause problems of the traffic system. The aim of this study was to identify the availability of parking spaces in Muar town, to provide quantitative assessment of parking in Muar town and to analyze the sufficiency of parking spaces in the selected area in Muar town. To achieve the first objective, the analysis was done using ArcMap, afterwards, the questionnaire was distributed to residents in Muar to achieved the second objective, and the third objectives was achieved by using Erlang’s Loss Model. From the results of studies using GIS software, areas of parking around the government offices and banks in Muar are digitized. This enables the residents in Muar to park their vehicles close to the destination they want to go. In addition, through the results obtained from questionnaires and Erlangâ€™s Loss Model, it is found that Muar has a shortage of parking problem. Therefore, some suggestion is given so that this problem can be solved by the authorities such as build a multi-storey car park and provides a manual of parking location to residents in Muar.